Peningkatan jiwa entrepreneurship bagi pengelola media komunitas - Nasution, Nadya Amalia; Wijaya, Toni Wijaya; Iptahudin, Iptahudin (Universitas Islam Negeri Raden Intan Lampung, 2022)
Entrepreneurial spirit in Indonesia is still very low, the ratio of entrepreneurship in Indonesia is still at the level of 3.74%, still lagging behind neighboring countries. The government targets that by 2024, Indonesia is expected to have an entrepreneurship ratio above 3.9%, to make this happen, the younger generation, especially students, will be the determining actors, considering that creativity is needed in entrepreneurship, such as students working in community media. This service is based on the idea that community media are indispensable for public knowledge, especially the academic community at the University level in Bandar Lampung city. Community media has a weakness, namely the difficulty of community media in covering news because they are still underestimated compared to mainstream media. But thanks to this, community media can live together with mainstream media and even fill each other's roles. In order to live sustainably, community media need to develop the business sector so that it can be independent and more developed. This is necessary to realize the sustainability and sustainability of community media. The service team deems it necessary to develop an entrepreneurial spirit in community media managers at the University in Bandar Lampung. This service activity lasted for 2 days. Consists of training, mentoring, to evaluation of activities. The target of the activity is 5 community media in Bandar Lampung.